Koala country : a story of an Australian eucalyptus forest - Dennard, Deborah; McKinnon, James (Norwalk, Conn. : Soundprints, 2000)
A mother koala and her joey feed and observe the other animal inhabitants of their fragile eucalyptus forest home.
Keywords: Koala -- Juvenile fiction; Koalas -- Fiction; Marsupials -- Fiction; Zoology -- Australia -- Fiction